Modern Trends in Qualitative and Quantitative Studies of Existential Isolation and Paths to Overcoming It - P.A. Averina (Современная зарубежная психология)
The article presents a review of modern research on the phenomenon of existential isolation in foreign studies. An attempt is made to analyze different methodological approaches in understanding the problem of existential isolation by foreign researchers. The socio-psychological model STEIM proposed by P. Helm is considered. Existential isolation, on the one hand, is associated with depression, anxiety, and accessibility to thoughts of death, and on the other hand, causes social avoidance and loss of hope for the possibility of being understood, which creates significant difficulties in helping people with this condition in psychotherapy. Cross-cultural research demonstrates that collectivist values can be a buffer against feelings of existential isolation. The Scandinavian tradition of studying existential loneliness is discussed, in which qualitative studies of older people predominate and the phenomenon is consistently found to be associated with the experience of meaninglessness and proximity to death. It is concluded that different schools study the same phenomenon, approaching its research from different angles. The need to establish a dialogue between research traditions for a holistic understanding of the phenomenon and a comprehensive exploration of the possibilities for overcoming the experience of existential isolation is emphasized.